Description of a new species of the Charaea coomani group (Coleoptera: Chrysomelidae: Galerucinae) from Vietnam with a key to species - Dinh Nguyen; Loan Ho; Son Nguyen (Biodiversity Data Journal, 2021)
The genus Charaea Baly is distributed in the eastern Palaearctic, Himalayas, China and adjacent countries of the Oriental Region. Currently, 59 species of the genus Charaea have been recorded. The species of Charaea is characterised with a robust tubular aedeagus that terminates with a more or less distinct apical process with the Charaea coomani group having an internal sac with long sharp lateral sclerites. Up to now, 13 species of this group have been described in the Oriental Region, four of which are found in Vietnam.Charaea dinhcuongi sp. nov. is described as a new species, based on specimens collected from Phu Quoc Island in southern Vietnam. Colour photographs of habitus and body details and DNA barcode sequences are presented. An identification key is provided for all Vietnamese species from the Charaea coomani group.